Biochemical synthesis of taxanes from mevalonate - Jing Li; Xiaonan Liu; Xiaoxi Zhu; Jiayu Liu; Lei Zhang; Nida Ahmed; Jian Qi; Bihuan Chen; Daliang Tang; Jinsheng Yu; Zhijin Fan; Huifeng Jiang (Synthetic and Systems Biotechnology)
Taxanes are kinds of diterpenoids with important bioactivities, such as paclitaxel (taxol®) is an excellent natural broad-spectrum anticancer drug. Attempts to biosynthesize taxanes have made with limited success, mainly due to the bottleneck of the low efficiency catalytic elements. In this study, we developed an artificial synthetic system to produce taxanes from mevalonate (MVA) by coupling biological and chemical methods, which comprises in vitro multi-enzyme catalytic module, chemical catalytic module and yeast cell catalytic module. Through optimizing in vitro multienzyme catalytic system, the yield of taxadiene was increased to 946.7 mg/L from MVA within 8 h and the productivity was 14.2-fold higher than microbial fermentation. By incorporating palladium catalysis, the conversion rate of Taxa-4(20),11(12)-dien-5α-yl acetate (T5α-AC) reached 48 %, effectively addressing the product promiscuity and the low yield rate of T5αOH. Finally, we optimized the expression of T10βOH in yeast resulting in the biosynthesis of Taxa-4(20),11(12)-dien-5α-acetoxy-10β-ol(T5α-AC-10β-ol) at a production of 15.8 mg/L, which displayed more than 2000-fold higher than that produced by co-culture fermentation strategy. These technologies offered a promising new approach for efficient synthesis of taxanes.